The riot act [videorecording (DVD)] - Parks, Devon; Parks, Devon; Parks, Devon; Cullen, Brett; Keener, Brandon, 1974-; Price, Connor, 1994- (Giant Interactive, 2019)
After an actor is killed in a small town, a mysterious actress arrives with a vaudeville troupe and seeks revenge for the act while learning that her intended victim is already being terrorized by someone or something else.